Greening the Economy in Afghanistan – Role of the Critical Mineral Mining Industry - Rinat Tantashev; Bahtiyor Eshchanov (Finanse i Prawo Finansowe)
This article explores the current state and future prospects of developing a green economy in Afghanistan, focusing on renewable energy and fossil resources. It also examines regional cooperation and Afghanistan’s politico-economic relations with its neighbors, especially Uzbekistan.